DETERMINING THE JURISDICTION OF COURTS IN A MULTIMODAL TRANSPORT CARRIAGE UNDER NIGERIAN LAW – CARDINAL IN AN AFRICAN CONTINENTAL FREE TRADE AREA - DAMILOLA OSINUGA, (Journal of Malaysian and Comparative Law, 2023)
The recent establishment of the African Continental Free Trade Area (‘AfCFTA’) was predicated on the belief that increased intra-African trade and market integration would benefit the continent. The pact is expected to increase intra-African trade by making Africa a single market, harnessing its immense potential of over a billion persons and the Gross Domestic Product of circa three trillion United States Dollars. Without access to markets and resources, growth and continued poverty in society will stagnate. Accordingly, transportation is essential to international trade and regional integration. Research shows that multimodal transportation could create a cheaper transportation option than unimodal transportation. According to statistics, multimodal transport can reduce transportation costs by circa 20%, help enhance effectiveness in transportation by 30%, reduce the risk of damage to cargo by 10%, and aid energy savings and emissions. The United Nations Economic Commission for Africa (UNECA), through its Regional Advisor on Trade, has advised that the establishment of Multimodal Transport Operators (MTOs) should be encouraged to ensure the non-interrupted flow of goods from the origin to the destination. This paper particularly focuses on the determination of the jurisdiction of multimodal transportation and the extent to which the current lack of a clear legal framework affects a predictable and foreseeable determination of the jurisdiction of courts. The research considers these issues at a time when African leaders have come together to sign an agreement for the establishment of the AfCFTA.